Domestic Demand and Export Performance in CEMAC: A country's sensitive case? - Kuikeu Oscar (African Scientific Journal, 2025)
Abstract To tackle the existing negative relationship between exports and domestic sales presents into the literature from a macroeconomic perspective building on export market share equations (the difference between exports and foreign demand), in CEMAC area the literature is based on a panel data appoach using a dynamic panel data model with an error correction mechanism. The meaningful of this empirical approach is to introduce a long term relationship in investigating this negative relationship between exports and domestic sales. To take into account the presence of the endogenous (the export market shares) among the explanatory a 2SLS is used for the presence of endogeneity bias. Nevertheless the main bias in this result coming from the particular panel data structure in CEMAC area. In fact, comparing with a times series approach on Gabonese economy one of the CEMAC’s economy its appears that Gabon concentrates at itself more than a half of total observations in CEMAC in investigating this negative relationship building on exports market share equation. While the literature seems to confirm the findings that the overall result seems to be country’s sensitive. Then considering this particular panel structure where just one country concentrates more than a half of total observations there is certainly a bias in CEMAC area results that point as industrialized countries a negative relationship between exports and domestic sales. Then the aim of this paper was to investigate this bias, for this purpose we consider a CEMAC area without Gabon and we finds that the relationship is remains negative but not already significant as well as in the symmetric relation, the conventional econometric relation confirming thus this bias. While in than the asymmetric relation, the non linear relation according thus results with a sample of CEMAC area at 5 in the present study and the preceding into the literature with the full members States in its appear that the relationship is negative and significant only for positive changes in domestic demand. Therefore the convenient interpretation of the nexxus substitution effect between domestic sales and exports in CEMAC is that during growth periods a rebound in domestic demand would translate into contraction of exports of around 66%. An comparable elasticity to the Gabonese case at 65% in times series modeling that permits confirms the coherence between our results and the one’s that exists into the literature. thus to mitigate the bias. Keywords : Exports market share ; dynamic panel data model ; country’s sensitve case ; bias ; symmetric relation ; asymmetric relation ; CEMAC